The Emerging Roles of Heterochromatin in Cell Migration - Gerlitz, Gabi (Frontiers in Cell and Developmental Biology, 2020)
Cell migration is a key process in health and disease. In the last decade an increasing attention is given to chromatin organization in migrating cells. In various types of cells induction of migration leads to a global increase in heterochromatin levels. Heterochromatin is required for optimal cell migration capabilities, since various interventions with heterochromatin formation impeded the migration rate of numerous cell types. Heterochromatin supports the migration process by affecting both the mechanical properties of the nucleus as well as the genetic processes taking place within it. Increased heterochromatin levels elevate nuclear rigidity in a manner that allows faster cell migration in 3D environments. Condensed chromatin and a more rigid nucleus may increase nuclear durability to shear stress and prevent DNA damage during the migration process. In addition, heterochromatin reorganization in migrating cells is important for induction of migration-specific transcriptional plan together with inhibition of many other unnecessary transcriptional changes. Thus, chromatin organization appears to have a key role in the cellular migration process.